Implementation Green Human Resource Management in Universities - Muhammad Rajab; Mohd Yusoff Yusliza (Greenation Research & Yayasan Global Resarch National, 2023)
The necessity of Green Human Resource Management in Universities cannot be denied, as it combines environmental management with Human Resource Management. Implementation of GHRM practices facilitates the rapid implementation of an EMS system for a University. This paper presents an understanding of the fundamental GHRM practices, as well as the practices that are specific to certain Universities and Higher Education Institutes. It also highlights the significance of implementing them. Proper implementation of a Green Human Resource Management system can raise awareness among staff and management about waste management, resource reduction, and maintaining campus cleanliness. A successful implementation can satisfy stakeholders, including employees, and motivate them to enhance their productivity.